High-Resolution Fibre Bragg Grating (FBG) Pressure Transducer for Low-Pressure Detection - Z. M., Hafizi; Vorathin, E.; A. M., Aizzuddin; K. S., Lim (Universiti Malaysia Pahang, 2019)
Fibre Bragg grating (FBG) pressure sensor has shown great potential in replacing the conventional electrical pressure sensor due to its adaptability to the harsh environment. However, increasing its resolution for low-pressure measurement is still a challenge. In this work, the bonding of FBG to a rubber-based diaphragm pressure transducer was proposed. The proposed pressure transducer had enhanced the sensitivity to 117.7 pm/kPa across the range of 40 kPa, which corresponded to the pressure resolution of 0.008 kPa. Furthermore, the proposed pressure transducer possessed a reference FBG for temperature compensation, where the overall temperature effect was less than 1%.